Enhancement of the Reliability of Extra and Ultra High Voltage Transmission Systems - Ramold, Mathias; Jäger, Johann (2009 IEEE Bucharest Power Tech Conference, 2009)
Single-pole auto-reclosing is an approved method to enhance the reliability in transmission systems. But with increasing system voltage, the maximum line length, for which a common single-pole auto-reclosing is successful, decreases. Therefore this paper will show how single-pole auto-reclosing can also be applied in extra and ultra high voltage transmission systems, by extending the system with high-speed grounding switches or with four-legged shunt reactor schemes. The operation mode of both will be illustrated. © 2009 IEEE.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.leen.enhanc
Keywords: Four-legged shunt reactor scheme; High-speed grounding switches; Secondary arc current; Single-pole auto-reclosing